2022
DOI: 10.3389/fpls.2022.882587
|View full text |Cite
|
Sign up to set email alerts
|

The hexokinase Gene Family in Cotton: Genome-Wide Characterization and Bioinformatics Analysis

Abstract: Hexokinase (HXK) is involved in hexose phosphorylation, sugar sensing, and signal transduction, all of which regulate plant growth and adaptation to stresses. Gossypium hirsutum L. is one of the most important fiber crops in the world, however, little is known about the HXKs gene family in G. hirsutum L. We identified 17 GhHXKs from the allotetraploid G. hirsutum L. genome (AADD). G. raimondii (DD) and G. arboreum (AA) are the diploid progenitors of G. hirsutum L. and contributed equally to the At_genome and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…The prediction of theoretical core sites for glucose and phosphate binding demonstrated that all homologous HXKs possessed the conserved AA residues (e.g., Asp-101, Gly-104, and Ser-177) except for AtHKL1 and PtHXK4, suggesting that PtHXK4 may be a catalytically inactive glucose sensor ( Figure 4 ). These results were supported by several recent works performed on Cassava, bamboo, and cotton [ 16 , 17 , 18 ]. These conserved features of HXKs may be more variable in gymnosperms, bryophytes, and lycophytes, suggesting that the plant-derived HXKs probably evolved from prokaryotic ancestors, common primordial actin fold protein [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The prediction of theoretical core sites for glucose and phosphate binding demonstrated that all homologous HXKs possessed the conserved AA residues (e.g., Asp-101, Gly-104, and Ser-177) except for AtHKL1 and PtHXK4, suggesting that PtHXK4 may be a catalytically inactive glucose sensor ( Figure 4 ). These results were supported by several recent works performed on Cassava, bamboo, and cotton [ 16 , 17 , 18 ]. These conserved features of HXKs may be more variable in gymnosperms, bryophytes, and lycophytes, suggesting that the plant-derived HXKs probably evolved from prokaryotic ancestors, common primordial actin fold protein [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 85%
“…edulis , Z . mays , A. thaliana , G. raimondii , M. esculenta , N. tobacum , S. lycopersicum , P. patens , and S. moellendorffii were obtained from the literatures [ 1 , 10 , 15 , 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HXKs family proteins play a key regulatory role in sugar sensing, sucrose metabolism, catalyzing hexose phosphorylation, providing energy and modulation of plant growth and stress adaptation [ 27 ]. HXK belongs to a multigene family and HXK is usually encoded by a medium family of approximately 4–10 genes in higher plant, i.e., six members of the HXK family were identified in A. thaliana [ 2 ], while it is represented by 10 members in O. sativa [ 28 ], nine members in Z. mays [ 29 ], nine members in Nicotiana tabacum [ 30 ], 17 members in Gossypium hirsutum L. [ 31 ] and 19 putative members in B. napus [ 32 ] ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…HXK gene family members have been systematically identified in various plant species. 10, 9, 4, 7, 11, 17 HXK genes members were identified respectively in Oryza sativa (Cho et al, 2006), Zea mays (Zhang et al, 2014), Lycopersicon esculentum (Kandel-Kfir et al, 2006), Manihot esculenta (Geng et al, 2017), Physcomitrella patens (Olsson et al, 2003) and Gossypium hirsutum L (Dou et al, 2022) in their genome.…”
Section: Introductionmentioning
confidence: 99%